Paradiopatra (Annelida: Onuphidae) from eastern Australian waters, with the description of six new species - Paxton, Hannelore; Budaeva, Nataliya (Zootaxa, 2013)
This study recognises eight species of Paradiopatra from eastern Australian waters, of which only one, Paradiopatra ehlersi, had been previously recorded. Six species are newly described: P. acirrata n. sp., P. imajimai n. sp., P. longicappa n. sp., P. piccola n. sp., P. spinosa n. sp., P. variabilis n. sp., and one species is reported as P. cf. papillata. Descriptions of all species (with the exception of P. ehlersi) are given, accompanied by detailed illustrations, including scanning electron micrographs and drawings. A key to all 32 species of the genus is included plus a table summarising specific diagnostic characters of the Australian representatives.